2000
DOI: 10.1021/jo001418i
|View full text |Cite
|
Sign up to set email alerts
|

Generation, Characterization, and Kinetics of Triplet Di[1,2,3,4,5,6,7,8-octahydro-1,4:5,8-di(ethano)anthryl]carbene

Abstract: The title carbene has been generated by photolysis of the corresponding diazo precursors and studied by spectroscopic means, i. e., electron paramagnetic resonance (EPR) and UV/vis spectroscopy in matrixes at low temperature and laser-flash photolysis in solution at room temperature, with the product analysis. The results are compared with triplet di(2,3,5,6-tetramethylphenyl)carbene, an open-chain counterpart, which revealed that bicycloalkyl groups are acting as a fairly good kinetic protector for the triple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 43 publications
1
11
1
Order By: Relevance
“…The decay rate ( k obs ) of 3 1a increased upon the addition of methanol. However, the plot of k obs versus methanol concentration was not linear for the concentration range of 2.47–9.22 M 44, 67. A plot of better linearity was observed when the k obs was plotted against the dimer concentration of methanol.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…The decay rate ( k obs ) of 3 1a increased upon the addition of methanol. However, the plot of k obs versus methanol concentration was not linear for the concentration range of 2.47–9.22 M 44, 67. A plot of better linearity was observed when the k obs was plotted against the dimer concentration of methanol.…”
Section: Resultsmentioning
confidence: 88%
“…It has been reported that the sharp peak due to the radical species around 330 mT is found when some triplet signals in 2‐MTHF at 77 K decrease by thawing the matrix 29, 30, 44. This means that the triplet diarylcarbenes decayed by abstracting a hydrogen from 2‐MTHF to form the corresponding diarylmethyl radicals.…”
Section: Resultsmentioning
confidence: 99%
“…Optical spectroscopy, which probes the manifold of electronically excited states, is another important technique for identification of reactive intermediates. Particularly transient absorption and UV/vis matrix isolation spectroscopy demonstrated their usefulness in studying reactive species like carbenes and nitrenes. Existing knowledge, of either experimental or computational nature, on the excited states is only available for diatomic borylenes (BH, BF, BCl, BBr, and BI). Most investigations have been performed on the excited states of parent borylene (BH), , including the experimental determination of the singlet–triplet energy splitting that was confirmed by sophisticated computations. ,, A number of studies concerning the electronically excited states of chloroborylene (BCl), fluoroborylene (BF), ,− and bromoborylene (BBr) , are available.…”
Section: Introductionmentioning
confidence: 99%
“…In other words, the larger the atomic number of the central carbenic atom, E, the more positive is the Δ E st for C 60 –E–C 60 . It should be noted that these M06-2X computations assume that the ground state of these fullerene carbenes C 60 –E–C 60 (E = C, Si, and Ge) should be a triplet state. This theoretical Δ E st data also demonstrates that the difference in energy between singlet and triplet state is quite small. In fact, as seen in Table , a comparison of the calculated structures for C 60 –E–C 60 in the singlet and triplet states suggests that one geometrical parameter (i.e., the bond angle, θ) allows the Δ E st value to have an important role in the C 60 –E–C 60 species.…”
mentioning
confidence: 73%